Zika knowledge and prevention practices among U.S. travelers: a large cross-sectional survey study - Maya Luetke; Oghenekaro Omodior; Erik J. Nelson (BMC, 2019)
Abstract Background The aim of this study was to investigate what factors predict knowledge about Zika transmission, symptomology, and treatment among U.S. travelers and, additionally, to evaluate how Zika knowledge influences the adoption of personal protective behaviors. Methods Data were collected as part of a cross-sectional survey study using a probability-based internet panel of U.S. travelers in June 2017. We ran logistic regression models of factors predicting Zika knowledge (high vs. low) and of knowledge predicting adoption of personal protective measures. Results We found that traveling to a Zika endemic country and travelers' gender were both significantly predictive of higher Zika knowledge (odds ratio (OR): 1.48, 95% confidence interval (CI): 1.14-1.93 and OR: 1.44, 95% CI: 1.08-1.92), adjusting for age, race, education, income, and trip purpose. Additionally, among travelers to Zika endemic countries, individuals with higher Zika knowledge had significantly higher odds of engaging in preventive behaviors compared to those with lower knowledge. However, few travelers knew about the sexual transmission of Zika and adopted sexual prevention measures. Conclusions Our findings suggest that there are gaps in knowledge about the risks and transmission of Zika and travelers with low knowledge are less likely to engage in the appropriate prevention methods. Significantly, few U.S. travelers have knowledge of the sexual transmission of Zika and, accordingly, there is less overall engagement with prevention measures for this transmission mechanism than for vector-borne transmission.